PENGEMBANGAN E-MODUL INTERAKTIF PADA MATA PELAJARAN BIOLOGI KELAS X DI SMA NEGERI 2 BANTAENG - Fatmawati, Nur; Pattaufi; Hakim, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of information and communication technology (ICT) has significantly impacted education, introducing more interactive and comprehensive learning methods. This study aims to 1) determine the level of need, 2) design an interactive e-module, and 3) assess the validation and practicality of the interactive e-module. The research employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques included interviews and questionnaires. The study subjects consisted of 2 validators (a media validator and a content validator), 20 tenth-grade students, and 1 teacher who teaches Biology. Validation results indicate that the developed interactive e-module is highly valid. The feedback from teachers and students suggests that the module is practical. The findings show that this e-module is both highly valid and practical for use in biology education, particularly in teaching abstract topics like viruses.